Diagnóstico y tratamiento quirúrgicos - Doherty, Gerard M. (McGraw-Hill's AccessMedicina., 2021)
Surgical Diagnosis and Treatment is an easy-to-read source of information on diseases handled by surgeons. Like other books in the Lange series, it emphasizes rapid recall of major diagnostic features, and brief descriptions of disease processes, followed by definitive diagnostic and treatment approaches. Epidemiology, pathophysiology, and pathology are addressed to the extent that they contribute to the ultimate purpose of the book, which is the guide to patient care. About a third of the book focuses on general medical and surgical issues important to the management of all patients.